PENYULUHAN KEWIRAUSAHAAN BIDANG EKONOMI KREATIF DALAM PEMBUATAN ANYAMAN TIKAR PANDAN DI DESA SEUNEUBOK ACEH - Roswita, Cut; Hanum, Erlia; Rahmawati; Aldyza, Nadia; Liana, Tuti; Afkar (LPPM Universitas Al Muslim, 2024)
The lack of entrepreneurial character in the community of Seuneubok Village, Aceh, is a problem and challenge for the team implementing community service activities, thus it considered necessary to empower PKK members consisting of housewives through providing counseling and training in making woven pandan mats and involving the community of Seuneubok Village, Aceh. The craft of woven pandan mats is the business of PKK women in Seuneubok Village, Aceh, which is a traditional commercial product that needs marketing strategies improvement to increase its high economic value. This activity aimed to improve entrepreneurial skills and improve the family economy. This activity was carried out by PKK members through the PKM program which was held on April 20 to May 28, 2024. Methods for implementing activities included friendly meetings, raw material surveys, visits and interviews, providing innovative input, and training in making woven pandan mats. This activity is expected to make a positive contribution to the welfare of families in Seuneubok Village, Aceh. The evaluation was carried out to measure the increase in participants' knowledge and skills, as well as the impact on the family economy. It is hoped that the results of this service can be an inspiring example for developing creative economic potential in other rural areas.